Technical and structural changes. The hypothesis of decreasing coefficients. Statistical tests with data for Mexico - Aroche Reyes, Fidel (Estudios Económicos de El Colegio de México, 1995)
Technical coefficients change basically due to technological changes —except when there are price differences. On the other hand, there are models maintaining the hypothesis that differences between coefficients along time will be negative. Mexican data provides clues for such statement, at least for long periods, although, evidence is not always consistent for short ones.